2006
DOI: 10.1007/s10389-006-0071-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effectiveness of different types of supported housing for patients with chronic schizophrenia

Abstract: Upward trend in tobacco use, particularly in women, is a reason for concern. In medical faculties, principles of prevention should be more emphasized and the students motivated for healthy life-style and to fulfill their future role in public health. The situation noted among medical students indicates that a community in Slovakia is still not satisfactory inclined towards non-smoking and a dramatic decrease of tobacco use can hardly be expected either in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
1
18
0
1
Order By: Relevance
“…During the last decade, decreasing trends of cigarette smoking have been observed among students, including those of medical sciences, in some countries such as US and Republic of Ireland (6,7), while other studies in Slovakia (8), Japan (9), and Brazil (10), have reported an increasing trends. …”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, decreasing trends of cigarette smoking have been observed among students, including those of medical sciences, in some countries such as US and Republic of Ireland (6,7), while other studies in Slovakia (8), Japan (9), and Brazil (10), have reported an increasing trends. …”
Section: Introductionmentioning
confidence: 99%
“…Non-English language papers were excluded to ensure faithful application of the taxonomies. The final pool consisted of 132 service descriptions across 101 papers (quantitative: 95 service descriptions across 72 papers; qualitative: 37 service descriptions across 29 papers) [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,…”
Section: Resultsmentioning
confidence: 99%
“…A total of 10 studies were selected for this review (Cooper & Pearce, 1996;Davison, McCabe, Knight, & Mellor, 2012;Depla, De Graaf, & Heeren, 2006;Depla, De Graaf, Van Weeghel, & Heeren, 2005;Kallert, Leisse, & Winiecki, 2007;Leisse & Kallert, 2000;Luzny & Ivanova, 2009;Nakagawa & Hayashi, 2013;Smalbrugge et al, 2006). Eight of these studies were cross-sectional studies, and two were longitudinal studies (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…All studies included participants with psychiatric diagnoses. Some studies investigated groups with specific diagnoses, such as major depressive disorder (Davison et al, 2012), depression and/or anxiety (Smalbrugge et al, 2006) or psychotic disorders (Kallert et al, 2007;Leisse & Kallert, 2000;Nakagawa & Hayashi, 2013). Other studies included people with a variety of diagnoses (Cooper & Pearce, 1996;Depla et al, 2006;Depla, De Graaf, Van Weeghel, & Heeran, 2005;Luzny & Ivanova, 2009).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation